(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The paper deals with a creep behavior of Pb – Sn eutectic alloy is studied. The creep experiments were executed at constant tensile stress (4.2, 5.5 and 6.5 MPa) in range of temperature 360 – 430K. From traditional analysis of steady – state creep is acquired the creep data. The curves creep are showed temperature effect, the stress sensitive variable, and evident activation energy of creep. The evident activation energy and stress exponent for creep were delimited as approximately 57 KJ/mole and 4 respectively. The values of n and Q are delicate to the process controlling creep deformation. Optical microscope was used to test the microstructure of samples before and after creep deformation to find the mechanisms of creep deformation. The strain of Pb-61.7wt%Sn is increased during creep test and according to subjected stress value. The best value of strain at 360K and in stress 6.5MPa about 0.3, also can be get little strain values at (360, 370,380,390K) and at 4.2MPa are (0.1,0.15, 0.2, 0.3) respectively.